A systematic review of methods to predict maximal oxygen uptake from submaximal, open circuit spirometry in healthy adults. Issue 2 (March 2015) - Evans, Harrison J.L.; Ferrar, Katia E.; Smith, Ashleigh E.; Parfitt, Gaynor; Eston, Roger G.
Abstract Objectives This systematic review aimed to (i) report the accuracy of submaximal exercise-based predictive equations that incorporate oxygen uptake (measured via open circuit spirometry) to predict maximal oxygen uptake (<alternatives><inline-graphic xlink:href="ark:/27927/pgj3wfpg35" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V˙O2 max</alternatives>) and (ii) provide a critical reflection of the data to inform health professionals and researchers when selecting a prediction equation. Design Systematic review. Methods A systematic search of MEDLINE, EMBASE (via OvidSP), CINAHL, SPORTDiscus™ (via EBSCO Host) and Scopus databases was undertaken in February 2013. Studies were required to report data on healthy participants aged 18–65 y. Following tabulation of extracted data, a narrative synthesis was conducted. Results From a total of 7597 articles screened, 19 studies were included, from which a total of 43 prediction equations were extracted. No significant difference was reported between the measured and predicted <alternatives><inline-graphic xlink:href="ark:/27927/pgj3wfpcjf" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V˙O2 max</alternatives> in 28 equations. Pearson's correlation coefficient between the predicted and measured <alternatives><inline-graphic xlink:href="ark:/27927/pgj3wfpcph" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V˙O2 max</alternatives> ranged from r = 0.92 to r = 0.57. The variables most commonly used in predictive equations were heart rate (n = 19) and rating of perceived exertion (n = 24). Conclusions Overall, submaximal exercise-based equations using open circuit spirometry to predict <alternatives><inline-graphic xlink:href="ark:/27927/pgj3wfpf88" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V˙O2 max</alternatives> are moderately to highly accurate. The heart rate and rating of perceived exertion methods of predicting <alternatives><inline-graphic xlink:href="ark:/27927/pgj3wfpgfb" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V˙O2 max</alternatives> were of similar accuracy. Important factors to consider when selecting a predictive equation include: the level of exertion required; participant medical conditions or medications; the validation population; mode of ergometry; time and resources available for familiarisation trials; and the level of bias of the study from which equations are derived.